Detox Fashion Case Studies - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This fourth volume on detox fashion focuses on case studies, which are essential to showcase how practical applications have been accomplished, and provide an opportunity for others to (learn about and) adopt the best practices, challenges and practical implications. The book consists of three core chapters: Detoxifying the Supply Chain: Slow Production Networks in South-East European Garment Factories; Detoxifying the Luxury and Fashion Industry: The Case of Market-driving Brands; and Detox My Fashion under Mission 2020-Case Studies from Different Brands.
1. Detoxifying the Supply Chains: Production networks of Slow Garment Factories in South-Eastern Europe -- 2.Detoxifying luxury and fashion industry: Case of market driving brands -- 3. Integrating Sustainable Strategies in Fashion Design by Detox 2020 plan - Case studies from Different Brands .
Keywords: Manufactures; Business logistics; Economic development; Environmental chemistry; Industrial engineering; Production engineering; Chemistry, Technical; Machines, Tools, Processes; Supply Chain Management; Development Studies; Environmental Chemistry; Industrial and Production Engineering; Industrial Chemistry